Tricks of the trade: time management tips for newly qualified doctors. Issue 1109 (26th October 2017) - Offiah, Gozie; Doherty, Eva
Abstract: Background: The transition from medical student to doctor is an important milestone. The discovery that their time is no longer their own and that the demands of their job are greater than the time they have available is extremely challenging. Methods: At a recent surgical boot camp training programme, 60 first-year surgical trainees who had just completed their internship were invited to reflect on the lessons learnt regarding effective time management and to recommend tips for their newly qualified colleagues. They were asked to identify clinical duties that were considered urgent and important using the time management matrix and the common time traps encountered by newly qualified doctors. Results: The surgical trainees identified several practical tips that ranged from writing a priority list to working on relationships within the team. These tips are generic and so applicable to all newly qualified medial doctors. Potential implication: We hope that awareness of these tips from the outset as against learning them through experience will greatly assist newly qualified doctors.